(untitled) (Biological Sciences - PJSIR, 2001)
The results of a road traffic noise survey carried out in Hyderabad city showed that the levels of traffic noise in the City are alarmingly high and much beyond the comfortable Iimits. Therefore, in order to investigate the level of the noise emitted by different types of vehicles plying on the city roads and to assess their individual contribution to high level traffic noise, studies have been carried out on the measurement of noise emitted by motorcycles, buses, auto-rickshaws, and motor vehicle horns as they normally move on the city roads. The data collected has been analyzed for LV<J!I.L,90.L,so.’ L,IO.and LVIand results are discussed with reference to the existing motor vehicle rules in Pakistan and motor vehicle noise emission limits set by the EEC and other developed countires. Some suggestions have also been made to limit high level traffic noise.